Burmese Amber Compared Using Micro-Attenuated Total Reflection Infrared Spectroscopy and Ultraviolet Imaging. Issue 7 (July 2021) - Musa, Maya; Kaye, Thomas G.; Bieri, Willy; Peretti, Adolf
Attenuated Total Reflection (ATR) spectroscopy coupled with a microscope allows for the analysis of specimens without any preparation, spatially correlated with the morphology of the specimen. These characteristics make micro-ATR systems very useful for studying gemstones and in particular amber samples. Indeed, in this report, the micro-ATR technique was used to characterize three Burmite samples, as case studies. Particularly, focusing the ATR crystal spot on the amber surface where a difference in the Ultraviolet (UV) reaction was previously detected, thereby relative differences in the IR spectrum could be analyzed. Here we present a methodology combining the UV imaging technique with the micro-Attenuated total reflection Fourier transform infrared spectroscopy (micro-ATR/FT-IR) analyses, in order to correlate the fluorescence information with the molecular vibrational modes of amber and their relative spatial distribution. Finally, this work is intended as an initial methodology study and part of the amber characterization project, focused on characterizing the Burmese amber collection of the Peretti Museum Foundation from several disciplines (i.e., palaeoentomology, vibrational spectroscopy, neutron tomography, etc.). Graphical Abstract